Sistem Informasi Pengiriman Barang Berbasis Web pada CV. Mustika Sarana - Pranata, Aldo (Program Studi Teknik Informatika Universitas Pamulang, 2022)
Cv. Mustika Sarana is a private service company engaged in the delivery of goods or expedition. Cv. Mustika Sarana is a freight forwarder from Jakarta with the aim of sending goods to several major cities on the island of Sumatra. Some of the destinations for delivery of goods include the cities of Lampung, Palembang, Jambi, Pekanbaru, Bukittinggi, and the city of Padang by land route. Currently the company is still not optimally computerized in the field of recording data and transactions, which causes frequent occurrences, errors in recording, data loss, and delays in reporting. Data processing is very influential on a company, because by having fast and accurate data processing, a lot of information can be taken from the data. If the company does not manage data optimally it will have a direct impact on senders and potential senders. Because the sender of the goods cannot know the condition of the delivery status of his goods and the prospective sender does not have an idea of the price, delivery destination, delivery route and duration. The purpose of this research is to create a Website-Based Goods Delivery Information System using the extreme programming (XP) method. The resulting delivery information system can be used to record shipping transaction data and shipping transaction information that is equipped with the status of the goods. So that the problems that exist in the Cv. Mustika Sarana can be overcome with this goods delivery information system.